Enhancing carbon capture efficiency of zeolite-embedded polyether sulfone mixed-matrix membranes via annealing process. (1st May 2023) - Sohail, Aamir; Sarfraz, Muhammad; Nawaz, Sidra; Tahir, Zaman
Abstract: Current work was motivated by rapid advancement in membrane technology for application of gas separation, that resulted in the formation of mixed-matrix membranes (MMMs) with higher selectivity and permeability. MMMs are one way to get above the Robeson upper bound of selectivity against permeability for gaseous separation while retaining the advantages of solution processing. Numerous inorganic materials like zeolites, carbon nanotubes, or metal-organic frameworks can behave as molecular sieves, but they are fragile and difficult to fabricate as standalone membranes. This problem might be solved by embedding them into a more durable polymeric membrane matrix. In this work, symmetric mixed-matrix membranes fabricated through solution casting technique were employed with zeolite A-3 dispersed in a polyether sulfone (PES) matrix. Impacts of zeolite loading and annealing temperatures on thermal stability, morphology and carbon capture performance of prepared membranes were systematically investigated. Carbon capture proficiency of fabricated membranes was assessed in terms of CO2 permeability and CO2 /N2 selectivity. In contrast to pristine PES membrane, incorporation of optimal 30 wt% zeolite into polymer matrix enhanced CO2 permeability from 81 to 128 Barrer and CO2 /N2 selectivity from 9 to 22. Annealing the composite membranes at 155 °C led to further enhance CO2 permeability at the expense of reduced CO2 /N2 selectivity: CO2 permeability of pristine PES membrane enhanced from 81 to 126 Barrer by decreasing its CO2 /N2 selectivity from 9 to 6; CO2 permeability improved from 128 to 144 Barrer while CO2 /N2 selectivity declined from 22 to 18 for composite membrane imbedded with 30 wt% optimum zeolite loading. Graphical abstract: Image 1 Highlights: Zeolite/PES MMMs were prepared via solution-casting cum phase inversion technique. Thorough dispersion of zeolite particles in PES matrix rendered good compatibility. Embedment of zeolite efficiently improved CO2 /N2 separation performance of MMMs. Annealing of MMMs further improved CO2 permeability at reduced CO2 /N2 selectivity. Enhanced carbon capture performance was obtained at optimum zeolite loading.